MODERN METHODS OF DIAGNOSTICS OF GLAUCOMA OPTIC NEUROPATHY IN CONGENITAL GLAUCOMA IN CHILDREN - Arzibekov Abdikadir Gulyamovich (Scholar Express Journals, 2025)
The article presents the results of application of modern highly informative methods of studying the structures of the posterior segment of the eye in various forms and stages of congenital glaucoma in children: the method of confocal laser scanning ophthalmoscopy (HRT), the technique of spectral optical coherence tomography (S-OCT). The obtained morphometric data and a number of pathognomonic symptoms of damage to the optic nerve, retina, choroid, main branches of the central artery (CRA) and central retinal vein (CRV) in congenital glaucoma are necessary for studying the pathogenesis of congenital glaucoma, clarifying the diagnosis, determining the prognosis of the disease, assessing the stabilization of the glaucomatous process and developing treatment tactics.
Keywords: congenital glaucoma; glaucomatous optic neuropathy